Kinerja Pegawai Kantor Dukcapil Kabupaten Malang Dilihat dari Gaya Kepemimpinan, Budaya Organisasi dan Disiplin Kerja - Prayogo Ahmad Hidayat; Sinollah; Gettik Andri Purwanti (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
This research aims to determine and analyze the influence of leadership style, organizational culture and work discipline on employee performance at the Malang Regency Population and Civil Registration Office. To achieve this goal, this research uses quantitative methods using multiple linear regression analysis. The research results show that partially leadership style has a significant effect on employee performance, partially organizational culture has a significant effect on employee performance, partially work discipline has no significant effect on employee performance, leadership style, organizational culture and work discipline have a simultaneous effect on employee performance. employee at the Malang Regency Population and Civil Registration Service